Recorded Remarks by World Bank Group President David Malpass at the World Government Summit 2022 - Malpass, David (World Bank, Washington, DC, 2022)
This report discusses the remarks delivered by World Bank Group President David Malpass at the World Government Summit 2022. He discusses: Middle East and North Africa (MENA) will soon be the epicenter of the upcoming climate action discussions, with Egypt hosting COP27 and UAE COP28. From a global perspective, more access to clean energy will be critical for development. 760 million people, many of whom live in the poorest countries, remain without access to electricity. Regional cooperation on energy can bring GCC financing and expertise to the rest of the MENA region. With the current situation in commodity markets, the fiscal bill for fuel subsidies will crowd out many other activities if left unreformed.